The kin system as a poverty trap? - Hoff, Karla Ruth, 1953- 1953- (Policy research working paper, 2005)
"An institution found in many traditional societies is the extended family system (kin system), an informal system of shared rights and obligations among extended family for the purpose of mutual assistance. In predominantly non-market economies, the kin system is a valuable institution providing critical community goods and insurance services in the absence of market or public provision. But what happens when the market sector grows in the process of economic development? How do the members of kin groups respond, individually and collectively, to such changes? When the kin system "meets" the modern economy, does the kin system act as a "vehicle of progress" helping its members adapt, or as an "instrument of stagnation" holding back its members from benefiting from market development? In reality, the consequences of membership in a kin group have been varied for people in different parts of the world. Hoff and Sen characterize the conditions under which the kin system becomes a dysfunctional institution when facing an expanding modern economy. The authors first show that when there are moral hazard problems in the modern sector, the kin system may exacerbate them. When modern sector employers foresee that, they will offer employment opportunities on inferior terms to members of ethnic groups that practice the kin system. These entry barriers in the market, in turn, create an incentive for some individuals to break ties with their kin group, which hurts members of the group who stay back in the traditional sector.